Ensuring the density coefficient in road foundation construction works - Kulmamatov Romazon Juma ogli,; Muhammadjonov Alijon Olimjonovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
There is talk of increasing the strength of the pavement using composite materials in the construction of the pavement and the study of foreign technologies.